Re-thinking the Technosol design for greenery systems: Challenges for the provision of ecosystem services in semiarid and arid cities - González-Méndez, Blanca; Chávez-García, Elizabeth (Journal of arid environments, 2020)
Many cities in developing countries in semiarid and arid regions are far more vulnerable to climate change. Thus, it is urgent to adopt mitigation strategies that allow diminishing these impacts. Greenery systems could contribute to many urban ecosystem services as the thermal performance of buildings, removal of atmospheric pollutants, stormwater management, and carbon sequestration, among others. Many of these ecosystem services are linked to soil functions, but until now, the most advanced knowledge about growing medium performance comes from temperate and subtropical cities, where commercial or engineering reasons have dominated the growing medium formulation. As artificial growing medium usually contains natural and human-made materials, they belong to the Technosols group and therefore are subject to the different pedogenetic processes. As a result of the mix of the used materials and variable environmental conditions to which they are exposed, Technosols could modify their properties and impact on the greenery system performance. To adapt the greenery system technologies to semiarid and arid cities, we present a review of the available information of growing medium formulation. We also propose to re-think the Technosol design from a pedological point of view, taking into account the soil quality framework, useful not only for the Technosol design but also for its monitoring performance through time. [Display omitted] •Greenery systems could help mitigate the climate change effects in semiarid and arid cities.•Urban ecosystem services, provided by greenery systems, are linked to growing medium functions.•The artificial growing medium usually contains human-made materials, being classified as Technosols.•Technosols have different pedogenetic processes that affect greenery system performance.•A soil quality framework could be used to Technosols formulation and monitoring of its performance.